Sustainable Development Through Community Participation in Coastal Area of Wonocoyo Village, Panggul Sub-District, Trenggalek District - Yusup Saktiawan (Postgraduate School Universitas Brawijaya, 2020)
The research objections are 1) Analyze supportive factors of sustainable development in a coastal area, Kili-Kili Garden Wonocoyo village, Panggul sub-district, Trenggalek district 2) Analyze forms and types of society involvement regarding the program inÂ Kili-Kili seabord garden. The method of collecting data are questionnaires, interview techniques, observation techniques, documentation techniques, and triangulation methods. The location of this research is situated in the Kili-Kili garden Wonocoyo village Panggul sub-district Trenggalek district. The result of the research shows community participation level on its coastal development is considered small with merely 1354 points.